Students’ Engagement dalam Proses Pembelajaran Daring Melalui Lesson Study pada Mata Kuliah Kalkulus Integral - Iin Ariyanti; Fikrie Fikrie; Dyta Setiawati Hariyono (Mathematics Education Study Program, 2022)
Students' engagement in the learning process is very important to identificate because it affects student success in the learning process. Students’ engagement is a psychological process that shows the attention, interest, investment, effort, and involvement of students which is poured into learning work includes emotional, cognitive, and behavioral engagement. This study aimed to see students' engagement in the online learning process through lesson study because from the beginning, the learning process had good planning (plan, do & see). This study used a qualitative-quantitative approach where the qualitative approach in this study aimed to produce an in-depth description of student engagement based on speech, writing and behavior observed by the observer during the stage of